EU-US Relations: Reinventing the Transatlantic Agenda - Steven Blockmans (Intereconomics, 2021)
With Joe Biden's victory, there is at least a four-year window to revive 'an alliance of democracies', face up to authoritarian powers and closed economies that exploit the openness on which American and European societies are built, and shape those parts of multilateralism that serve transatlantic interests.
Keywords: 330; EU-Außenpolitik; EU-Außenwirtschaftspolitik; EU-Staaten; USA